3 - Institutionalising Terror in the Name of Religion and Polity: The Nigerian Youth and the Cosmos of Violence - Sanni, Amidu (Africa Development, 2021)
Religion and ethnicity are two key issues in the economy of violence with which Nigeria has had to contend in the last twenty-five years. The protagonists of the issues are the state, the aficionados of reli- gious or ethnic idealism and their opponents. The article argues that the culture of denial or marginalisation has largely been responsible for the tradition of violence, which militant and radical elements in religious and ethnic circles have often employed in their systemic campaigns. It concludes by submitting that a proper appreciation of the real causes of violence by the state, and a genuine commitment to their solution through dialogue and interactive means, remains the viable option in the enthronement of world peace and order.